'Dis ain't gimme, Florida': Zora Neale Hurston's Their Eyes Were Watching God - Newman, Judie (Modern Humanities Research Association, 2003)
Who owns Zora Neale Hurston? That was the question asked in 1990 by Michele Wallace, in an analysis of the ways in which Hurston has been appropriated by later scholars. Wallace's pungent comparison of later critics to so many 'groupies descending on Elvis Presley's estate' in their haste to turn Hurston to their own purposes strikes a cautionary note for any subsequent writer. As she notes, the risk of canonization is that the work will be misused to derail the future of blackwomen in literature and literary criticism. For Wallace, Harold's introduction to his Modern Critical Views anthology of 1986 is a case in point.